Analysis of Fintech and Digital Bank Collaboration on the Increase of Third-Party Funds: A Case Study of GoPay and Bank Jago Integration - Febriansah Febriansah; Roikhan Mochamad Aziz; Ade Ananto Terminanto; Ady Cahyadi; Muhammad Juang Harfian; Halimatus Sa’diyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
The digital transformation of the financial sector has spurred innovative collaborations between financial technology (fintech) firms and digital banks, creating new paradigms for growth. A primary challenge for digital banks is the rapid and cost-effective acquisition of Third-Party Funds (DPK), which is crucial for liquidity and lending capacity. This study addresses the problem of how strategic integration between a super-app's fintech arm and a digital bank can serve as an effective mechanism for accelerating DPK growth. The research objective is to conduct an in-depth analysis of the collaboration model between GoPay, a leading fintech platform in Indonesia, and Bank Jago, a technology-based bank, and its subsequent impact on Bank Jago's DPK accumulation. This research employs a qualitative case study methodology, using secondary data analysis of audited financial statements, official corporate press releases, reputable industry reports, and academic literature. The findings reveal that the seamless integration of Bank Jago's services into the Gojek super-app ecosystem functions as a highly efficient customer acquisition funnel. This model significantly lowers traditional barriers to banking, converting millions of transactional e-money users into formal bank depositors. The analysis of Bank Jago's financial data demonstrates a substantial and sustained increase in its TPF, particularly in low-cost Current Account Savings Account (CASA) funds, following the strategic integration. This study concludes that the embedded finance model, as exemplified by the GoPay-Jago partnership, represents a powerful strategy for digital banks to achieve scalable DPK growth by leveraging the vast user base and high engagement frequency of a super-app ecosystem.